ANALISIS PERBANDINGAN PRODUKSI SEBELUM DAN SETELAH WELLSERVICE PADA SUMUR X LAPANGAN Y PT PERTAMINA EP - Yehuda Eric Christian; Laksmita Sari, Riska (Petroleum Engineering, Faculty of Engineering, University of Jember, 2024)
Well X started production on February 9th, 2012 with oil production of 217 BOPD and peak production on March 1th, 2012 with oil production of 2756 BOPD. As production progresses, the reservoir pressure will decrease resulting in a decrease in the production rate. Well X was shut-in on March 7th, 2023 with oil production of 197 BOPD and watercut reaching 91.27%. The location of this study is administratively located in Campurejo Village, Bojonegoro District, Bojonegoro Regency. Analysis of well potential and well forecasting are carried out by the Wiggins method. This method was chosen because the X well has a three-phase fluid and a high water cut. The calculation results show a maximum flow rate of 4111.52 BFPD and an optimum flow rate of 2466.91 BFPD. After calculating the optimum flow rate, and to avoid water cloning, it is recommended that wells be produced with a production flow rate of 2412.54 BFPD at a well base flow pressure (Pwf) of 1368 Psi. Keyword: well service; IPR; future IPR